Elevated Homocysteine and the Risk of Contrast-Induced Nephropathy: A Cohort Study. (April 2015) - Barbieri, Lucia; Verdoia, Monica; Schaffer, Alon; Niccoli, Giampaolo; Perrone-Filardi, Pasquale; Bellomo, Giorgio; Marino, Paolo; Suryapranata, Harry; Luca, Giuseppe De
Contrast-induced nephropathy (CIN) is a common complication in patients with impaired kidney function undergoing coronary angiography/angioplasty. We evaluated whether elevated homocysteine (known to be associated with free radical generation and oxidative stress) increases the risk of CIN. Patients (n = 876) with creatinine clearance <60 mL/min undergoing coronary angiography or percutaneous coronary intervention (PCI) were divided into tertiles of homocysteine levels. Contrast-induced nephropathy was defined as ≥0.5 mg/dL or ≥25% creatinine increase 24 to 48 hours post-PCI. A significant relationship was observed between homocysteine levels and the risk of CIN ( P = .033), confirmed after correction for baseline confounding factors, adjusted odds ratio, OR (95% confidence interval, [CI]) = 1.68 (1.09-2.59), P = .019. This association was also significant applying the new definition of contrast-induced acute kidney injury (11.9% in group 1, 10.4% in group 2, and 22.8% in group 3; P < .001), adjusted OR (95% CI) = 1.96 (1.3-2.95), P = .001. Future studies are needed to confirm our findings and to define the role of homocysteine in CIN.